CERTAIN ASPECTS OF COUGH PATHOGENETIC THERAPY OF ACUTE CHILD RESPIRATORY INFECTIONS - S.I. Bardenikova; O.V. Zaitseva; L.N. Novozhilova; E.E. Lokshina; T.I. Rychkova; I.G. Stepanova (Вопросы современной педиатрии, 2008)
An open controlled comparative research was conducted on 263 children with acute respiratory infection (ARI) in order to evaluate the clinical effectiveness, acceptability and safety of plant based preparation that contains ivy leaf extract. It was established that prescribing the preparation during the first days of disease reduced the duration of dry and inefficient cough, improved sputum rheology and bronchial tree drainage function, reduced bronchial obstruction intensity, reduced the need for prescribing bronchial spasmolitics less necessary and decreased Staybin term. Compared to other antibcough medicines, plant based preparation with ivy leaf extract has quicker effect (effective on the 1st–3rd day).Key words: children, acute respiratory infections, cough, treatment.